Binary Synergistic Sensitivity Strengthening of Bioinspired Hierarchical Architectures based on Fragmentized Reduced Graphene Oxide Sponge and Silver Nanoparticles for Strain Sensors and Beyond. Issue 28 (31st May 2017) - Zhao, Songfang; Guo, Lingzhi; Li, Jinhui; Li, Ning; Zhang, Guoping; Gao, Yongju; Li, Jia; Cao, Duxia; Wang, Wei; Jin, Yufeng; Sun, Rong; Wong, Ching‐Ping
Abstract : Recently, stretchable electronics have been highly desirable in the Internet of Things and electronic skins. Herein, an innovative and cost‐efficient strategy is demonstrated to fabricate highly sensitive, stretchable, and conductive strain‐sensing platforms inspired by the geometries of a spiders slit organ and a lobsters shell. The electrically conductive composites are fabricated via embedding the 3D percolation networks of fragmentized graphene sponges (FGS) in poly(styrene‐ block ‐butadiene‐ block ‐styrene) (SBS) matrix, followed by an iterative process of silver precursor absorption and reduction. The slit‐ and scale‐like structures and hybrid conductive blocks of FGS and Ag nanoparticles (NPs) provide the obtained FGS–Ag‐NP‐embedded composites with superior electrical conductivity of 1521 S cm −1, high break elongation of 680%, a wide sensing range of up to 120% strain, high sensitivity of ≈10 7 at a strain of 120%, fast response time of ≈20 ms, as well as excellent reliability and stability of 2000 cycles. This huge stretchability and sensitivity is attributed to the combination of high stretchability of SBS and the binary synergistic effects of designed FGS architectures and Ag NPs. Moreover, the FGS/SBS/Ag composites can be employed as wearable sensors to detect the modes of finger motions successfully, and patterned conductive interconnects for flexible arrays of light‐emitting diodes. Abstract : A highly sensitive, stretchable, and conductive strain‐sensing platform is designed and inspired by the geometry of spiders and lobsters. The slit‐like and fragmentized structures provide the strain sensor with superior electrical conductivity (1521 S cm −1 ), a wide sensing range (120% strain), high sensitivity (≈10 7 at strain of 120%), and fast response time (≈20 ms), showing potential in stretchable electronics.